A retrospective cohort study investigating the association of environment, milk performance and udder health with the yield and solid content of first-milking colostrum in Holstein dairy cows - Gonçalo Pereira; Ricardo Bexiga (BMC Veterinary Research)
Abstract Background The administration of high-quality colostrum is widely recognized as crucial for the health and survival of neonatal calves, yet identifying factors influencing colostrum yield and solid content has remained a challenge. With dairy farmers facing increasing difficulties in maintaining a year-round supply of high-quality colostrum, this retrospective cohort study evaluated the association between environmental, milk performance, and udder health factors with colostrum yield and solid content (as measured by Brix % determination) in 1731 lactations of Holstein dairy cows (583 primiparous and 1148 multiparous) on a commercial farm. Results In primiparous cows, colostrum yield was associated with the time interval between calving and colostrum collection (as estimated by whether colostrum was collected during morning or afternoon milking), while lower colostrum solid content was associated with higher occupancy of the close-up pen. In multiparous dairy cows, both colostrum yield and solid content were associated with lactation number (higher lactations associated with lower yield but with higher solid content), dry period length (longer dry periods associated with higher yield and higher solid content), and whether colostrum was collected during morning or afternoon milking. A lower colostrum solid content of multiparous cows was also associated with higher occupancy of the close-up pen and a higher colostrum yield was associated with higher THI during the 21 days before calving. Moreover, greater milk yield at dry-off was associated with lower colostrum yield and a longer previous calving interval was associated with greater colostrum yield. These findings highlight the benefits of longer dry periods and calving intervals for colostrum production, the need to revise dry-off practices for high-yield dairy cows, and the importance of addressing overpopulation in close-up pens, especially in heat-stressed herds with higher variation in close-up pen occupancy. This work also reinforces the importance of shorter intervals between calving and colostrum collection for higher solid content of colostrum in multiparous cows. Conclusions Overall, this study enhances understanding of the factors influencing colostrum production and provides valuable insights for developing improved colostrum management strategies.